Josie and the Pussycats. Volume two - Bennett, Marguerite; Deordio, Cameron (Archie Comic Publications, 2018)
Follows the graphic novel adventures of Josie and the Pussycats as they are kidnapped and taken to Cabotopia in Antarctica, almost make it to the music awards, and have a wild visit to Tokyo. Along the way, the group sees familiar faces, learns the true meaning of friendship, and finds success doing things their own way.